Performance of carbendazim removal using constructed wetlands for the Ethiopian floriculture industry - Stan Wehbe; Feleke Zewge; Yoshihiko Inagaki; Wolfram Sievert; N.T. Uday Kumar; Akshay Deshpande (Water Science and Technology, 2022)
Carbendazim is a pesticide commonly used in Ethiopian flower farms and has harmful effects on aquatic, invertebrate, and mammalian life. Previous studies have explored ways to remedy carbendazim toxicity; however, the use of constructed wetland (CW) systems for carbendazim removal from farm water runoff has not been explored in depth. The primary aim of this study was to investigate the efficacy of a CW system for carbendazim removal from wastewater runoff. A two-stage pilot CW was built and tested for its efficacy of carbendazim removal under saturated conditions and varying hydraulic loading rates. The influent was pumped into the first vertical-flow mesocosm. The drained water was then pumped into the second mesocosm. The collected effluent was tested for carbendazim removal. Carbendazim removal efficiencies up to 91.80% (with a hydraulic loading rate of 100 Ld−1 and influent carbendazim concentration of 10 μg L−1) were observed. Statistical analysis indicated that the removal of carbendazim was not correlated with the initial carbendazim concentration but was negatively correlated with the hydraulic loading rate used. Two pesticide removal mechanisms were briefly probed to determine their participation in carbendazim removal. Substrate sorption accounted for 18% of total carbendazim removal; furthermore, plant uptake also played an active role. HIGHLIGHTS Novel two-stage pilot-scale constructed wetland was built to reflect industry standard configuration of constructed wetlands.; Tests under saturated conditions showed up to 91.80% carbendazim removal from the influent water.; Carbendazim removal efficiency was found to be positively correlated with a higher hydraulic retention time but to be independent of the influent carbendazim concentration.;